Influence of lysine level fed from 40 to 80 lb on growth performance and carcass composition of barrows and gilts - Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 1,200 pigs was used to determine the influence of lysine level fed from 40 to 80 Ib on growth performance and carcass composition. Barrows and gilts were fed com-soybean meal-based diets with 6% added fat formulated to .80, .95, 1.10, 1.25, or 1.40% total lysine. Increasing dietary lysine improved ADG and F/G in a linear and quadratic manner with optimal ADG at 1.10% lysine and optimal F/G at 1.400/0 lysine. Economic returns over feed costs were similar at 1.10, 1.25, and 1.40% lysine.
Keywords: Swine; Lysine; Growing-finishing pig; Growth